Association of timing of gabapentinoid use with motor recovery after spinal cord injury. (15th December 2020) - Warner, Freda M.; Cragg, Jacquelyn J.; Jutzeler, Catherine R.; Grassner, Lukas; Mach, Orpheus; Maier, Doris D.; Mach, Benedikt; Schwab, Jan M.; Kopp, Marcel A.; Kramer, John L.K.
Abstract : Objective: To explore the hypothesis that earlier administration of acute gabapentinoids is beneficial to motor recovery after spinal cord injury in humans. Methods: This is an observational study using a cohort from the European Multi-Centre Study about Spinal Cord Injury. Patient charts were reviewed to extract information regarding the administration and timing of gabapentinoid anticonvulsants. The primary outcome measure was motor scores, as measured by the International Standards for Neurological Classification of Spinal Cord Injury, collected longitudinally in the first year after injury. Sensory scores (light touch and pinprick) and functional measures (Spinal Cord Independence Measure) were secondary outcomes. Linear mixed effects regression models included a drug-by-time interaction to determine whether exposure to gabapentinoids altered recovery of muscle strength in the first year after injury. Results: A total of 201 participants were included in the study and had a median age of 46 and baseline motor score of 50. Participants were mostly men (85%) with sensory and motor complete injuries (50%). Seventy individuals (35%) were administered gabapentinoids within the first 30 days after injury, and presented with similar demographics. In the longitudinal model, the administration of gabapentinoids within 30 days after injury was associated with improved motor recovery when compared to those who did not receive gabapentinoids during this time (3.69 additional motor points from 4 to 48 weeks after injury; p = 0.03). This effect size increased as administration occurred earlier after injury (i.e., a benefit of 4.68 points when administered within 5 days). Conclusions: This retrospective, observational study provided evidence of the beneficial effect of gabapentinoid anticonvulsants on motor recovery after spinal cord injury. More critically, it highlighted a potential time dependence, suggesting that earlier intervention is associated with better outcomes. Classification of evidence: This study provides Class IV evidence that gabapentinoids improve motor recovery for individuals with acute spinal cord injury.